Passive acoustic records of seafloor methane bubble streams on the Oregon continental margin. (April 2018) - Dziak, R.P.; Matsumoto, H.; Embley, R.W.; Merle, S.G.; Lau, T.-K.; Baumberger, T.; Hammond, S.R.; Raineault, N.
Abstract: We present acoustic records of methane bubble streams recorded ~10 km southwest of Heceta Bank on the Oregon continental margin using an autonomous hydrophone. The hydrophone was deployed at 1228 m water depth via a Remotely Operated Vehicle (ROV) during the E/V Nautilus expedition (NA072) in June 2016. Bubble sound is produced by detachment of the gas bubble from the end of a tube or conduit which causes the bubble to oscillate, producing a sound signal. Despite persistent ship propeller and ROV noise, the acoustic signature of the overall bubble seep site can be seen in the hydrophone record as a broadband (1.0 – 45 kHz) series of short duration (~10–20 ms) oscillatory signals that occur in clusters lasting 2–3 s. The frequency of an individual bubble's oscillation is proportional to the bubble's radius; estimates here of bubble radii are consistent with bubble sizes observed in ROV still images. Acoustic signal loss models imply bubble sounds might be recorded over an area of seafloor from ~300 – 3.2 × 10 4 m 2 . This study represents a first-step in attempting to identify and quantify deep-ocean bubble stream sounds using passive acoustic techniques.